Pilot Study to Predict Pharmacokinetics of a Therapeutic Gemcitabine Dose From a Microdose. Issue 8 (22nd January 2020) - Van Nuland, M.; Rosing, H.; Thijssen, B.; Burgers, J.A.; Huitema, A.D.R.; Marchetti, S.; Schellens, J.H.M.; Beijnen, J.H.
Abstract: Microdose studies are exploratory trials to determine early drug pharmacokinetics in humans. In this trial we examined whether the pharmacokinetics of gemcitabine at a therapeutic dose could be predicted from the pharmacokinetics of a microdose. In this prospective, open‐label microdosing study, a gemcitabine microdose (100 µg) was given intravenously to participants on day 1, followed by a therapeutic dose (1250 mg/m 2 ) on day 2. Gemcitabine and its metabolite 2', 2'‐difluorodeoxyuracil (dFdU) were quantified in plasma and intracellularly by using liquid chromatography‐mass spectrometry). Noncompartmental pharmacokinetic analysis was performed. Ten patients participated in this study. The mean area under the plasma concentration‐time curve (AUC0‐8 ) of gemcitabine after microdosing was 0.00074 h·mg/L and after therapeutic dosing was 16 h·mg/L. The mean AUC0‐8 of dFdU following the microdose and therapeutic dose were 0.022 h·mg/L and 169 h·mg/L, respectively. Exposure to gemcitabine after the therapeutic dose was within 2‐fold of the exposure following a microdose, when linearly extrapolated to 1250 mg/m 2 . However, the shape of the concentration‐time curve was different, as reflected by poor scalability in volume of distribution (939 L versus 222 L). Furthermore, intracellularly phosphorylated gemcitabine and phosphorylated dFdU levels could not be predicted from the microdose. The AUC0‐8 of gemcitabine at therapeutic dose was accurately predicted by the pharmacokinetics of a microdose, when linearly extrapolated to 1250 mg/m 2 . Volume of distribution, elimination rate constant, and intracellular pharmacokinetics of the therapeutic dose could not be predicted from the microdose, which demonstrates limitations of the microdose approach in this case.